Simulation of a Heat Pump Dryer for Medicinal Plants1. Issue 3 (15th November 2012) - Ziegler, Thomas; Jubaer, Hasan; Mellmann, Jochen
Abstract Partially open and closed cycle modes of heat pump drying of medicinal plants were investigated theoretically as well as in industrial practice and were assessed from an energetic point of view. A simulation model was developed and validated with measurements performed at an industrial dryer. Design and control parameters for operation in partially open mode were calculated and implemented. Case studies for different operating conditions revealed that the partially open mode is more energy‐efficient than the closed cycle mode. Comparisons with conventional drying ascertained the feasible ambient conditions for heat pump operation. Almost all probable meteorological conditions during the drying season in Germany were covered in the analyses.